2019
DOI: 10.1186/s12957-018-1540-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific risk factors contributing to early and late recurrences of intrahepatic cholangiocarcinoma after curative resection

Abstract: BackgroundMost intrahepatic cholangiocarcinoma (ICC) patients experienced tumor recurrences even after curative resection, but the optimal cut-off time point and the specific risk factors for early and late recurrences of ICC have not been clearly defined. The objective of the current study was to define specific risk factors for early and late recurrences of ICC after radical hepatectomy.MethodsIncluded in this study were 259 ICC patients who underwent curative surgery at our hospital between January 2005 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 28 publications
8
42
1
Order By: Relevance
“…In this retrospective study, 409 (4.3%) developed purely local recurrence, 325 (3.4%) developed purely regional recurrence, and 182 (1.9%) developed locoregional recurrence, which is similar to the results of previous studies from other centers in China ( 12 , 13 ); 192 patients (46.9%) developed early ETR, and 217 patients (53.1%) developed LTR, 183 patients (56.3%) developed ENR, and 142 patients (43.7%) developed LNR, while 87 patients (47.8%) developed ELR, and 95 patients (52.2%) developed LLR, which suggests that the incidence of early and late recurrence is nearly the same. The patients with LTR/LNR/LLR demonstrated significantly better OS than the patients with ETR/ENR/ELR, which is consistent with previous studies on renal cell carcinoma and intrahepatic cholangiocarcinoma ( 14 , 15 ), while post-recurrence OS did not reach significance between the ETR and LTR, ENR and LNR, and ELR and LLR groups, which suggests that post-recurrence OS does not depend on the time of recurrence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this retrospective study, 409 (4.3%) developed purely local recurrence, 325 (3.4%) developed purely regional recurrence, and 182 (1.9%) developed locoregional recurrence, which is similar to the results of previous studies from other centers in China ( 12 , 13 ); 192 patients (46.9%) developed early ETR, and 217 patients (53.1%) developed LTR, 183 patients (56.3%) developed ENR, and 142 patients (43.7%) developed LNR, while 87 patients (47.8%) developed ELR, and 95 patients (52.2%) developed LLR, which suggests that the incidence of early and late recurrence is nearly the same. The patients with LTR/LNR/LLR demonstrated significantly better OS than the patients with ETR/ENR/ELR, which is consistent with previous studies on renal cell carcinoma and intrahepatic cholangiocarcinoma ( 14 , 15 ), while post-recurrence OS did not reach significance between the ETR and LTR, ENR and LNR, and ELR and LLR groups, which suggests that post-recurrence OS does not depend on the time of recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…developed LLR, which suggests that the incidence of early and late recurrence is nearly the same. The patients with LTR/LNR/LLR demonstrated significantly better OS than the patients with ETR/ENR/ELR, which is consistent with previous studies on renal cell carcinoma and intrahepatic cholangiocarcinoma (14,15), while post-recurrence OS did not reach significance between the ETR and LTR, ENR and LNR, and ELR and LLR groups, which suggests that post-recurrence OS does not depend on the time of recurrence. Multivariate Cox regression analysis revealed that age and gender were independent risk factors for OS with ETR, and the baseline value of EBV-DNA was an independent risk factor for OS with LTR; alcohol abuse and TNM stage were independent risk factors for OS with ENR, and no clinical characteristics were associated with OS with LTR, and N stage and TNM stage were independent risk factors for OS with ELR; and T stage was an independent risk factor for OS with LLR.…”
Section: Figure 3 |supporting
confidence: 89%
“…Scholars have not yet come to a consensus regarding the prognostic factors of cHCC-CCA. Although previous studies have confirmed that microvascular invasion (MVI) is a prognostic factor for tumor recurrence and is associated with poor survival outcomes in HCC [ 11 14 ] and ICC [ 15 , 16 ], the relationship between prognosis and the presence of MVI in cHCC-CCA patients has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…A cut-off of 1 year after resection has been used in previous studies to distinguish the early and late recurrence (31,32). Patients relapsed within 1 year after initial resection may represent more aggressive tumor biology.…”
Section: Discussionmentioning
confidence: 99%